2007
DOI: 10.1016/j.bpc.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of binding and catalysis for the Cdc25B phosphatase

Abstract: Using a combination of steady-state and single-turnover kinetics, we probe the temperature dependence of substrate association and chemistry for the reaction of Cdc25B phosphatase with its Cdk2-pTpY/CycA protein substrate. The transition state for substrate association is dominated by an enthalpic barrier (ΔH ‡ of 13 kcal/mol) and has a favorable entropic contribution of 4 kcal/mol at 298K. Phosphate transfer from Cdk2-pTpY/CycA to enzyme (ΔH ‡ of 12 kcal/mol) is enthalpically more favorable than for the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The calculated free-energy barrier is 17 kcal/mol. This value is identical to the barrier determined experimentally . In fact, H + transfer is well-advanced, but not complete, in comparison to phosphate transfer in the transition state.…”
Section: Resultssupporting
confidence: 84%
“…The calculated free-energy barrier is 17 kcal/mol. This value is identical to the barrier determined experimentally . In fact, H + transfer is well-advanced, but not complete, in comparison to phosphate transfer in the transition state.…”
Section: Resultssupporting
confidence: 84%
“…As shown in Figure 1A , the amounts of lysine (Lys), arginine (Arg) and Glycine (Gly) that are in acetylation samples are much higher than that of in non-acetylation samples. Indeed, a protein that has a surface that is composed mainly of negatively charged amino acids will bind to a protein with mainly positively charged molecules, such as lysine and arginine [44] , [45] , [46] , [47] , [48] . This shows that the acetylation substrates which bind to KATs are much different from non-acetylation.…”
Section: Resultsmentioning
confidence: 99%
“…However, an experimental investigation of the temperature dependence of binding of Cdc25B with pNPP does not support this notion. Sohn and Rudolph [53] found that the binding free energy of pNPP with Cdc25B was −8 kcal mol −1 , suggesting that although binding of phosphate at the active site is somewhat weak, the formation of the Michaelis complex is thermodynamically favorable. As discussed previously, our classical MD simulations of Cdc25 and two other PTPases provide evidence to support the unique preference of Cdc25 for the monoanionic form of small molecule substrates such as pNPP.…”
Section: Resultsmentioning
confidence: 99%